AHSS welding using undermatching filler wires and process advantages with P-GMAW. (2022) - John, Merbin; P, Ashok Kumar; K, Udaya Bhat
Abstract: The major challenge during welding of advanced high strength steels (AHSS) is finding an appropriate low cost filler wire which minimizes the softening in the heat affected zone (HAZ). The fabricators always prefer undermatching wires to join the thinner sections. This study reports the differences in the microstructure and mechanical properties of Ti-Nb microalloyed steel prior welded using pulse gas metal arc welding (P-GMAW) and standard gas metal arc welding (GMAW). The results indicate that the microalloyed steel welded using P-GMAW has inherent advantage over the standard GMAW. The pulses intensified the vibration perturbation in the weld puddle which cause microstructural refining and increased formation of the acicular ferrite (AF) constituent. The higher percentage of AF present in the weldment resisted propagation of the crack during static tensile test. Microhardness, ultimate tensile strength and joint efficiency during P-GMAW are much higher than the samples welded by standard GMAW.